CONTROLLED RANDOMIZED CLINICAL TRIAL ON USING TALISADI TAILAM FOR TREATING PATIENTS OF TINEA PEDIS W.S.R TO ALASA (AYUSHDHARA, 2021)
Skin is the general covering of the entire external surface of the body. Because of a large number of its functions, the skin is regarded as an important organ of the body. There are so many skin disorders of which Tenia pedis is a very common fungal infection that affects a significantly large number of people globally. This fungal infection is called Athlete’s foot because it is commonly seen in athletes. In Ayurveda, various skin disorders are described under the heading of kshudraroga. A brief description about Kshudraroga has been given in many Ayurvedic classics. Alasa is a variety of Kshudraroga occurring in between the skin of toes manifesting with Kleda, Kandu, Daha and Ruja. Talisadi tailam mentioned in Sushruta Samhita is an excellent formulation prepared of drugs which are effective against this disease. Current study includes 30 patients from OPD Department of Shalya Tantra, Jammu Institute of Ayurveda and Research, Jammu and Sri Sain Charitable Hospital, Janipur, Jammu diagnosed to have Tenia pedis based on signs and symptoms. Therapeutic effect was evaluated before and after treatment. The present clinical study has shown symptoms of Kandu, Daha, Ruja, Kleda significantly reduced after application of Talisadi tailam.